2021
DOI: 10.1186/s12958-021-00738-9
|View full text |Cite
|
Sign up to set email alerts
|

Thin endometrium is associated with the risk of hypertensive disorders of pregnancy in fresh IVF/ICSI embryo transfer cycles: a retrospective cohort study of 9,266 singleton births

Abstract: Background Thin endometrial thickness (EMT) has been suggested to be associated with reduced incidence of pregnancy rate after in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) treatment, but the effect of thin endometrium on obstetric outcome is less investigated. This study aims to determine whether EMT affects the incidence of obstetric complications in fresh IVF/ICSI-embryo transfer (ET) cycles. Methods We conducted a retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…At present, advanced maternal age (38,39), high levels of BMI (40,41), and a thin endometrium (42)(43)(44) as risk factors for adverse pregnancy outcomes are well recognized in the literature. Therefore, multivariate logistic regression analyses in our study were performed to exclude the potential influences of these confounding factors, but the effect of PCOS phenotypes A and D on adverse pregnancy outcomes persists.…”
Section: Discussionmentioning
confidence: 99%
“…At present, advanced maternal age (38,39), high levels of BMI (40,41), and a thin endometrium (42)(43)(44) as risk factors for adverse pregnancy outcomes are well recognized in the literature. Therefore, multivariate logistic regression analyses in our study were performed to exclude the potential influences of these confounding factors, but the effect of PCOS phenotypes A and D on adverse pregnancy outcomes persists.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in a previous study [ 18 ], the first follow-up was performed around 14 d after FET, and biochemical pregnancy was assessed by measuring the serum HCG-beta subunit. The second follow-up was performed at 5 or 6 weeks after embryo transfer; a clinical pregnancy was confirmed by the presence of a gestational sac by transvaginal ultrasound.…”
Section: Methodsmentioning
confidence: 99%
“…EMT is a key factor influencing endometrial receptivity and is a predictor of early pregnancy outcomes in ET cycles [ 16 ]. Furthermore, our previous studies demonstrate that thin EMT is associated with small for gestational age infants and hypertensive disorders of pregnancy in fresh ET cycles [ 17 , 18 ]. Another study from our clinic shows that women with a singleton delivery after FET in artificial cycles had an elevated risk of pre-eclampsia and postpartum hemorrhage compared with those in natural cycles [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by Miwa et al (26), it was found that vascular endothelial growth factor was underexpressed in a thin endometrium (<8 mm), leading to poor vascularization of the endometrium and impaired placentation. Apart from pathophysiology, several studies have shown that pregnancies conceived with a thin endometrium using assisted reproductive technology (ART) are at an increased risk of pregnancy loss, hypertensive disorders of pregnancy, preterm delivery, placenta previa, and cesarean section (27)(28)(29)(30). Additionally, infants conceived in these pregnancies are at risk of intrauterine growth restriction, being small for gestational age, and a lower birth weight (28,(31)(32)(33).…”
Section: Obstetric and Neonatal Outcomesmentioning
confidence: 99%